2021
DOI: 10.3390/nu13020571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Bitter Receptors Responsible for Epicatechin Detection Are Associated with BMI in an Elderly Cohort

Abstract: Globally, more than one-third of adults are overweight. Overweight and obesity are complex and multifaceted conditions, associated with an increased risk of chronic illness and early mortality. While there are known risk factors, these alone do not fully explain the varying outcomes between individuals. Recently, taste receptors have been proposed to have a role in the risk for obesity. These receptors are expressed throughout the gastrointestinal tract. In this system, they may be involved in modulating dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…It is unclear from the present data whether the variation in coffee bitterness seen for this haplotype results from the functional alteration of T2R5 or influences on transcription that alters the expression 36 . Additionally, recent studies in this allele have revealed that TGAG homozygotes show a significantly lower body mass index 37 38 .…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…It is unclear from the present data whether the variation in coffee bitterness seen for this haplotype results from the functional alteration of T2R5 or influences on transcription that alters the expression 36 . Additionally, recent studies in this allele have revealed that TGAG homozygotes show a significantly lower body mass index 37 38 .…”
Section: Resultsmentioning
confidence: 56%
“…36 Additionally, recent studies in this allele have revealed that TGAG homozygotes show a significantly lower body mass index. 37 The bitterness of alcohol is known to be the major taste component that influences alcohol consumption. 38 Choi et al showed an association between the TAS2R5 rs2227264 variant and total alcohol intake.…”
Section: Genomic Analyses Of Tas2rmentioning
confidence: 99%
“…Furthermore, this book also included a cross-sectional study to investigate the multidirectional interactions between TAS2R genotype [TAS2R4 gene (rs2233998 and rs2234001); TAS2R5 gene (rs2227264)], epicatechin intake, and body mass index (BMI), together in an elderly cohort. This study demonstrated that there is not an association between epicatechin intake and BMI and TAS2R genotype [8].…”
mentioning
confidence: 48%
“…These significant associations may suggest relevance for bitter-taste receptor genotype in the modulation of innate immunity and inflammatory pathways [29,30,34,[37][38][39]. Moreover, the bitter agonist, epicatechin (detected by TAS2R4-rs2234001 and TAS2R5-rs2227264 [53]), may be associated with the modulation of inflammatory pathways [60]. However, further studies are needed to evaluate these associations in oral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA samples were stored at −20 • C before genotyping. Genotyping was completed via qPCR (QuantStudio 7 Flex Real-Time PCR) with TaqMan SNP Genotyping assays (Applied Biosystems™, Thermo-Fisher Scientific, Waltham, MA, USA) and TaqMan™ Genotyping Master mix as per the TaqMan™ user's guide [52,53]. Complete genotyping was a mandatory inclusion criterion for this study.…”
Section: Genotypingmentioning
confidence: 99%